The role of professional logics in quality register use: a realist evaluation - Ann-Charlott Norman; Mattias Elg; Annika Nordin; Boel Andersson Gäre; Beatrix Algurén (BMC, 2020)
Abstract Background Clinical practice improvements based on quality-register data are influenced by multiple factors. Although there is agreement that information from quality registers is valuable for quality improvement, practical ways of organising register use have been notoriously difficult to realise. The present study sought to investigate the mechanisms that lead various clinicians to use quality registers for improvement. Methods This research involves studying individuals' decisions in response to a Swedish programme focusing on increasing the use of quality registers. Through a case study, we focused on heart failure care and its corresponding register: the Swedish Heart Failure Register. The empirical data consisted of a purposive sample collected longitudinally by qualitative methods between 2013 and 2015. In total, 18 semi-structured interviews were carried out. We used realist evaluation to identify contexts, mechanisms, and outcomes. Results We identified four contexts - registration, use of output data, governance, and improvement projects - that provide conditions for the initiation of specific mechanisms. Given a professional theoretical perspective, we further showed that mechanisms are based on the logics of either organisational improvement or clinical practice. The two logics offer insights into the ways in which clinicians choose to embrace or reject certain registers' initiatives. Conclusions We identified a strong path dependence, as registers have historically been tightly linked to the medical profession's competence. Few new initiatives in the studied programme reach the clinical context. We explain this through the lack of an organisational improvement logic and its corresponding mechanisms in the context of the medical profession. Implementation programmes must understand the logic of clinical practice; that is, be integrated with the ways in which work is carried out in everyday practice. Programmes need to be better at helping core health professionals to reach the highest standards of patient care.